The estructural marks of El mártir del sacramento, san Hermenegildo, by Sor Juana Inés de la Cruz: versification, sing and scenography - Mackenzie Rebollo, Carlos Enrique (2018)
In this paper, the structural function of El martir del sacramento, san Hermenegildo’s sung parts was analyzed. Attached to unusual metric forms and sumptuous scenographic elements, the sung parts of this auto are important to the story development. The combination of these elements indicates an important space overlap, leadingus from the inner conflicts of Hermenegildo to the impact of these on the outside.